Pulse Shape Dependence on Applied Voltage of Geiger-Mueller Detector - (:unkn) unknown (INT FREQUENCY SENSOR ASSOC-IFSA, 2019)
Geiger-Mueller (GM) detector is one of the oldest radiation detectors that is still being used extensively in the radiation measurement field. The detector was introduced in 1928 by scientists: Geiger and Mueller. It is assumed that all pulses generated by the GM counter are of the same size and shape. There is a general belief that the generated pulse shape characteristics do not carry any useful information. In this study, pulse shape characteristics (Pulse Width, Tail of Pulse, and Amplitude) were observed under various applied voltages under different radiation sources. It has been shown that the amplitude of the generated pulses by the GM detector increases with increasing the applied voltage for Co-60 and Cs-137 sources, unlike the background radiation.
Keywords: Deadtime correction; Geiger Muller counter; Radiation measurement; Pulse shape